The endoplasmic reticulum chaperone PfGRP170 is essential for asexual development and is linked to stress response in malaria parasites. (6th June 2019) - Kudyba, Heather M.; Cobb, David W.; Fierro, Manuel A.; Florentin, Anat; Ljolje, Dragan; Singh, Balwan; Lucchi, Naomi W.; Muralidharan, Vasant
Abstract: The vast majority of malaria mortality is attributed to one parasite species: Plasmodium falciparum . Asexual replication of the parasite within the red blood cell is responsible for the pathology of the disease. In Plasmodium, the endoplasmic reticulum (ER) is a central hub for protein folding and trafficking as well as stress response pathways. In this study, we tested the role of an uncharacterised ER protein, PfGRP170, in regulating these key functions by generating conditional mutants. Our data show that PfGRP170 localises to the ER and is essential for asexual growth, specifically required for proper development of schizonts. PfGRP170 is essential for surviving heat shock, suggesting a critical role in cellular stress response. The data demonstrate that PfGRP170 interacts with the Plasmodium orthologue of the ER chaperone, BiP. Finally, we found that loss of PfGRP170 function leads to the activation of the Plasmodium eIF2α kinase, PK4, suggesting a specific role for this protein in this parasite stress response pathway.